“Sorge um die Seele”. Incorporating Officers from Post-Migration Backgrounds in the German Police - Thériault, Barbara (Eurostudia)

(untitled) (Le Centre canadien d'études allemandes et européennes, 2008)
AbstractThe aim of this article is primarily a pragmatic one: to analyse police work by investigating the ways diversity is dealt with in the civil service in Germany, a country often described as hostile to diversity. In doing so from the standpoint of the police officers who contribute, through their work, in educating, recruiting, and counseling officers from post-migration backgrounds, the article sheds light on how change happens within the organization. At the center of this article is an ideal-type of one of the ways, or techniques, drawn upon when dealing with diversity in the police.